The matrix water space of mitochondria in situ in isolated hepatocytes. Issue 1 (January 1987) - Lund, Patricia; Wiggins, David
Abstract : The intracellular and mitochondrial matrix water-permeable spaces were measured in intact, respiring hepatocytes from normal fed, 48 h starved, and protein fed rats. The mitochondrial matrix constitutes 15–20 % of the total intracellular water, a proportion greater than has generally been assumed.